Use of literature in developing learner's speaking skills in Bangladeshi EFL contexts - Ainy, Salma (2007)
This dissertation arises from an attempt to answer the question whether it is possible to teach conversational skills through literature; and, if 'yes', how any benefit can be made accessible to both privileged and non-privileged sections of society. The stimulus for the present study derives from the view that, in order to develop the capacity of students in the EFL language class, the teaching of language should be taught using literary pieces and should move away from a teacher-centred approach towards a student-centred one. Having used an activity-based and process-oriented integrated approach as a framework, the present study illustrates the impact of the proposed way of literature teaching in an EFL context, specifically in the context of Bangladesh. It is designed to encourage students to experience literary texts directly as a part of a process of meaning creation that develops their thought processes, imaginative faculties and interpretative skills and ultimately has a strong impact on their speaking ability. Such a systematic approach to literature teaching in developing learner's speaking skills, therefore, is likely to enable teachers to have a more student-centred classroom. The present study also utilises the devised teaching activities based on prediction initiating personal growth, in an actual teaching/learning context in a selected research environment and explores students' responses to the proposed approach. The study groups involved in the research consist of two comparable groups: an experimental group (EO) and a control group (CG). The EG was exposed to the proposed teaching approach, whereas the CG followed the usual traditional teaching methods. The data for the study were gathered through interviews, questionnaires, observation sheets and field notes. Qualitative and quantitative investigation techniques were applied to the data and they were compared and contrasted for both the groups. The analyses of the data revealed significant differences between the groups in the nature of the students' responses to the teaching approaches. It was observed that there was a considerable relationship between the teaching methodologies employed in both classes, and levels of motivation, involvement and appreciation of the literary text under study and finally in the development in oral expression. The findings suggested that application of the teaching approach proposed by the study notably changed the classroom dynamics in a positive way.